The origins of association football in Ireland, 1875–1880: a reappraisal. Issue 4 (2nd October 2017) - Moore, Martin
ABSTRACT: According to its foundation myth, association football was introduced to Ireland when one man, John McAlery, personally organised an exhibition match between two Scottish teams in Belfast in 1878 and went on to form the first Irish association club in 1879 and the Irish Football Association in 1880. Based on new research, this article seeks to revise this traditional account, by presenting evidence of earlier association matches, including one in 1875: the earliest recorded association match thus far discovered. It also uses primary sources and a critical re-examination of secondary sources to re-evaluate the role of McAlery, and suggests that others ought also to be credited for the efforts that were made to establish association football in Ireland from the mid-1870s. The article also considers, but dismisses, other extant claims of early association football in Ireland, and, taking stock of recent scholarship, points to the existence of other more informal, less organised and less successful processes of diffusion in Ireland, prior to and contemporaneous to, but independent of, that which was ultimately successful in Ulster.